2007
DOI: 10.1158/0008-5472.can-06-2622
|View full text |Cite
|
Sign up to set email alerts
|

Depleting Intratumoral CD4+CD25+ Regulatory T Cells via FasL Protein Transfer Enhances the Therapeutic Efficacy of Adoptive T Cell Transfer

Abstract: One strategy for improving adoptive therapy is preconditioning the host immune environment by depleting CD4 + CD25 + regulatory T cells (Treg) suppressive to antitumor responses. Given that Treg increase, or selectively accumulate, within tumors and are sensitive to FasL-mediated apoptosis, we test here the hypothesis that inducing apoptosis of intratumoral Treg using FasL may improve adoptive T cell therapy. We show that FasL applied intratumorally via protein transfer decreases intratumoral Treg via inducing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(34 citation statements)
references
References 33 publications
1
33
0
Order By: Relevance
“…This sensitivity of Tregs to CD95-induced apoptosis is consistent with those in different publications where CD95-mediated apoptosis of Tregs was investigated in different disease settings (14,15,17). Chen et al (15) were interested in the effect of CD95-mediated depletion of Tregs in the tumor environment. They engineered cancer cells to display CD95L on their cell surfaces that could kill Tregs at the tumor site whereas control cells could not.…”
Section: Murine Tregs Are Sensitive To Cd95-mediated Cell Death In Vivosupporting
confidence: 80%
See 2 more Smart Citations
“…This sensitivity of Tregs to CD95-induced apoptosis is consistent with those in different publications where CD95-mediated apoptosis of Tregs was investigated in different disease settings (14,15,17). Chen et al (15) were interested in the effect of CD95-mediated depletion of Tregs in the tumor environment. They engineered cancer cells to display CD95L on their cell surfaces that could kill Tregs at the tumor site whereas control cells could not.…”
Section: Murine Tregs Are Sensitive To Cd95-mediated Cell Death In Vivosupporting
confidence: 80%
“…Although gld mice display elevated Treg numbers, the latter was unaltered in lpr mice (12,13). Moreover, several in vivo studies demonstrated that Treg numbers decline during an immune response as a result of CD95 ligation, whereas others claimed that CD95L expression by Tregs induces responder cell death in vitro (14)(15)(16)(17). Therefore, although the CD95/CD95L system seems to play a role in Treg homeostasis, existing discrepancies need to be resolved.…”
Section: Foxp3mentioning
confidence: 99%
See 1 more Smart Citation
“…It is conceivable that it may be advantageous to use antibodies or fusion proteins to reduce the action of Tregs at the local sites in combination with chemoprevention drugs to gain the maximal benefit during treatment of gastric cancer, even though we did not perform functional inhibition studies of Treg cells on host cytototic cells. Chen et al [42] have induced apoptosis of Tregs in a lymphoma animal model using intratumorally injecting FasL protein to deplete Tregs in the tumor and tumor-draining lymph nodes. Viehl et al [43] have also depleted Tregs by intraperitoneal injection with PC61 three times a week, in combination with tumor vaccine.…”
mentioning
confidence: 99%
“…Because IDO can be induced by IFN-g, IDO-negative cancer cells may be initiated to express IDO when exposed to an inflammatory context in the tumor microenvironment, and thereby hinder CD8 þ T-cell-mediated tumor regression before it can be effective (4,5,12). Recently, strong evidence has indicated that modification of the tumor microenvironment, such as the blockade of the TGF-b signaling pathway (15,16), inhibition of IDO (17,18), or depletion of Tregs (19,20) is able to augment the cytotoxicity of CD8 þ T cells.…”
Section: Introductionmentioning
confidence: 99%